Hindlimb Osteometry of Lohmann Broiler on 7, 21 and 35 days - Hanafi, Ulfiani Fauzia; Dhamayanti, Yeni; Soeharsono, Soeharsono; Wibawati, Prima Ayu; Prastiya, Ragil Angga (Jurnal Medik Veteriner, 2021)
Patterns of growth can be determined one of them through quantitative measurements, namely osteometry. The aim of this study was to determine the growth of patterns of Lohmann broiler chickens based on hindlimb osteometry at the age of 7, 21 and 35 days. This study used 30 Lohmann broiler chickens aged 7, 21 and 35 days. Osteometry techniques are performed on all the bones of hindlimb with variable Greatest length (GL), Breadth of the proximal end (Bp), Breadth of the distal end (Dd), Minimum breadth of diaphysis (Sd), Circular of the proximal end (Cp), Circular of corpus (Cc), and Circular of distal end (Cd). The data obtained is recorded in units of centimeters (cm). Data of body weight and weight of each bone are also recorded in grams (g). Data were analyzed by ANOVA test, if the result obtained with a significance of 5% then the test continued with Pos Hoc Duncan. The results showed that from 6 osteometry variables, body weight, and bone mass obtained significant differences (p<0.05). The fastest growth rate is reached when Lohmann broiler chickens are 21 days old.